2005
DOI: 10.1071/mf04083
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of primary production in the Daly River, a relatively unimpacted tropical river in northern Australia

Abstract: In this paper, the dynamics of primary production in the Daly River in tropical Australia are investigated. We used the diurnal-curve method for both oxygen and pH to calculate photosynthesis and respiration rates as indicators of whole-river productivity. The Daly River has maximum discharges during the summer, monsoonal season. Flow during the dry season is maintained by groundwater discharge via springs. The study investigated how primary production and respiration evolve during the period of low flow in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 27 publications
8
55
2
Order By: Relevance
“…1) lies in the Northern Territory of Australia with an area of 53 000 km 2 , including an extensive area of seasonally inundated floodplain. The hydrology of the river is driven by a highly seasonal monsoonal pattern of flow, with > 90% of annual rainfall occurring in the wet monsoonal period (approximately November to April) (Webster et al 2005, Warfe et al 2011. During the wet season monsoon, inundation allows for the movement of fish from the main river channel onto the floodplain (Warfe et al 2011).…”
Section: Field Trialsmentioning
confidence: 99%
“…1) lies in the Northern Territory of Australia with an area of 53 000 km 2 , including an extensive area of seasonally inundated floodplain. The hydrology of the river is driven by a highly seasonal monsoonal pattern of flow, with > 90% of annual rainfall occurring in the wet monsoonal period (approximately November to April) (Webster et al 2005, Warfe et al 2011. During the wet season monsoon, inundation allows for the movement of fish from the main river channel onto the floodplain (Warfe et al 2011).…”
Section: Field Trialsmentioning
confidence: 99%
“…Aquatic plants, including algae and other microbial primary producers, are notoriously leaky, losing large quantities of assimilated nutrients to the environment (Khailov and Burlakova 1969, Larsson and Hagstrom 1979, Descy et al 2002, Webster et al 2005. If material exuded by primary producers in the Ichetucknee River differs in elemental composition from standing biomass, as has been observed in other systems (e.g., transparent exopolymers with high C:N; Passow 2002), then our expectation that ecosystem and organismal stoichiometry will match is invalid.…”
Section: Ecosystem Stoichiometrymentioning
confidence: 99%
“…Because most natural and pristine streams or rivers around the world are shallow with low nutrient concentrations, a high canopy cover, and low phytoplankton biomass, light-limited benthic algae tend to dominate primary production. Light availability is commonly reported to be the dominant limiting factor, rather than nutrients or temperature, in stream and river ecosystems, especially in habitats with subsaturated irradiance (Mosisch et al 2001;Webster et al 2005). In addition to the effects of scouring floods that removed algal biomass, we found that shade from the riparian canopy cover was another key driver of algal growth at all study sites.…”
Section: Effects Of Light Availabilitymentioning
confidence: 50%
“…These influences can affect physical and biogeochemical processes, the food-web structure, and ecosystem metabolism (Webster et al 2005;Huang et al 2007;Yang et al 2009). Global warming is expected to change the spatial and temporal patterns of precipitation, to increase the intensity of storms and precipitation, and to reduce the duration of sunshine in tropical and subtropical regions (Kerr 2007;Zhang et al 2007).…”
Section: Introductionmentioning
confidence: 99%